Post partum female with sudden-onset breathlessness. Issue 2 (June 2020) - Deokar, Kunal; Niwas, Ram; Chawla, Gopal; Chauhan, Nishant
A 31-year-old, married female was admitted with complaints of sudden-onset shortness of breath and dry cough since that morning. It was not associated with chest tightness, wheezing or pleuritic chest pain. There was no history of fever, running nose or haemoptysis. The patient had undergone lower-segment caesarean section 2 weeks previously and had reduced mobility since then. She was known to have hypothyroidism for the past 3 years, which was well controlled on thyroxine. On admission, the patient had a respiratory rate of 30 per min, pulse rate of 130 per min, blood pressure of 110/70 mmHg and oxygen saturation by finger pulse oximetry of 89% on room air. Arterial blood gases on ambient air revealed pH of 7.48, carbon dioxide tension of 30 mmHg, oxygen tension of 58 mmHg and bicarbonate of 22 mEq·L −1 . Chest radiography did not reveal any significant abnormality. ECG revealed sinus tachycardia, right-axis deviation and T-wave inversion in leads V1–V4. Management of pulmonary embolism in post partum females is a challenge. Lower segment caesarean section in past 3 weeks is a contraindication to systemic thrombolysis. Heparin, fondaparinux and warfarin can be safely used in breast-feeding mothers. http://bit.ly/39Nr7qY